The Effect of Job Stress and Individual Characteristics on Performance with Emotional Intelligence as a Moderating Variable in Employees of the Sales Division of PT Multi Guna Nusantara - Kaban, Persadan Canisus; Siswanti, Yuni; Widjanarko, Hendro (UPN Veteran Yogyakarta, 2023)
This study aims to analyze the effect of job stress and personal characteristics on the performance of salespeople who reduce the emotional intelligence of PT Multi Guna Nusantara. This study utilizes a quantitative approach by collecting facts and statistics through a survey conducted with a questionnaire. For this analysis, we only included sales staff in the department with a total of 53 employees. The sampling method used was census, i.e. surveying the population as a whole. The analysis technique used in this research is Structural Equation Modeling (SEM) using Partial Least Squares (PLS) 3.0. The following are the results of this study: 1). There is job stress that has a significant impact on performance 2). There is a significant positive effect of individual characteristics on performance, 3). Emotional intelligence plays a role in moderating the impact of job stress on employee performance and 4). Emotional intelligence also moderates the impact of individual characteristics on employee performance.